FORMULATION AND ASSESSMENT OF A SUNSCREEN CREAM BASED ON GREEN TEA AND MARIGOLD FLOWER EXTRACTS - Akshay V. Rasal; Amol Kumar A. Kempwade Madhuri Sankpal
This study focuses on in vitro screening of aqueous and ethanolic extracts from green tea leaves and marigold petals for anti-solar potential using UV method. Ethanolic extracts were prepared via maceration, and evaluated for SPF. UV-1700 spectrometer was used to assess SPF and readings were averaged from triplicates. Extracts revealed significant phytoconstituents; green tea had SPF 11.90408, marigold had 7.56912, both guarding against carcinogenic UV radiation. Creams with ethanolic extracts show promising anti-solar activity, a natural alternative to synthetic sunscreens.